The effectiveness of soybean juice in reducing insomnia in premenopausal mothers - Sandiya Ferlina; Ellyda Rizki Wijhati (Jurnal Ners, 2025)
Women entering premenopause will experience a decrease in the hormone estrogen. This causes problems with premenopausal syndrome, especially physical complaints such as insomnia. Insomnia is a sleep disorder that makes it difficult for a person to sleep even though they have the desire to do so. Preliminary studies show that 73.3% of premenopausal mothers complained of sleep disorders such as difficulty falling asleep, waking up too early and feeling unrefreshed when they woke up. The aim of this study is to determine the effectiveness of soybean juice in reducing insomnia in premenopausal mothers. The research design used was a pre-experimental method with a one group pre-test post-test design type. The data analysis was carried out using the Wilcoxon Signed Ranks Test statistical test. The sampling technique used was purposive sampling with a total sample of 31 premenopausal mothers. The results of the study showed that consumption of soybean juice had an effect on reducing insomnia experienced by premenopausal mothers with a significance value of 0.000 (ρ < 0.05). This showed that there was a significant effect before and after giving soybean juice. Isoflavones in soybean juice have biological activity similar to estrogen and bind to estrogen receptors (ERs) as agonists. Stimulated estrogen receptor ERα by isoflavones, the interaction affects the cell transcription process so that there was stimulation of neurons in the central nervous system and resulted in a reduction in insomnia